Pengembangan Komik Edukatif Sistem Tata Surya Untuk Mengungkap Dampak Polusi Cahaya Pada Siswa SMP - Wardani, Putri Dyah Pramastya; Raida, Sulasfiana Alfi (WASIS : Jurnal Ilmiah Pendidikan, 2025)
The purpose of this research was to develop and test the feasibility of the educational science comic "The Adventures of Lintang and Gatra in the Solar System," which discusses the solar system and the impact of light pollution. This innovation was based on the low understanding of the material by seventh-grade students at SMP 2 Jekulo, due to the dominance of conventional learning and the lack of interactive visual media, despite the students' preference for comics. This research employed a research and development (R&D) method. The development was conducted using the 4D model, consisting of the stages of define, design, develop, and dissemination. The data collection process involved two types of data: quantitative and qualitative. Quantitative data were obtained from product validation conducted by experts (media, materials, and practitioners). Qualitative data were obtained from various suggestions and input provided by experts. Data collection instruments included validation instruments (media experts, material experts) and questionnaires from teacher and student responses. The validation results indicated high feasibility: material experts (94.55% very valid), media experts (95% very valid), and practitioners (933.33% very feasible). Positive responses from seven students (94.44%) indicated that the comic was engaging, easy to understand, relevant, and effective in increasing interest and independence in learning. The educational comic "The Adventures of Lintang and Gatra in the Solar System" proved to be highly valid and feasible as an innovative solution at SMP 2 Jekulo. This medium effectively increased students' understanding of the abstract concept of the solar system and raised awareness of light pollution issues.